The Relationship of Host and Environmental Factors to Events Dengue Hemorrhagic Fever - Dwi Julianti, Thamami; Ena Sari, Rumita; Lesmana, Oka; Hidayati, Fajrina; Eka Putri, Fitria (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: DHF cases are still in the high category and the number of morbid cases and the distribution of exposed areas is increasingly widespread. Indonesia's Health Profile data shows that there are 143,184 cases of DHF in Indonesia throughout 2022. This number has jumped 94.8% compared to the previous year. Objective: The purpose of this study was to determine the relationship between host and environmental factors with the incidence of dengue hemorrhagic fever in the Working Area of ??the Pamenang Health Centre, Merangin Regency. Methods: This research is a quantitative research with a cross approach sectional Results: The results showed that there was no relationship between age (p-value=0.653 and PR=0.944), education (p-value =0.677 and PR=0.677), knowledge (p-value=0.661 and PR=0.661), economic status (p-value =0.686 and PR=0.874), occupancy density (p-value =0.782 and PR=0.828), and clean water facilities (p=0.269 and PR=0.663). Then, there is a relationship between nutritional status (p=0.029 and PR=1.217), DHF prevention measures (p-value =0.037 and PR=1.646), air humidity (p-value =0.046 and PR=1.714), waste storage facilities (p-value = 0.037 and PR = 1.432), wastewater disposal facilities (p-value = 0.015 and PR = 1.471), on the incidence of dengue hemorrhagic fever in the Work Area Pamenang Health Centre. Conclusion: It is concluded that there is no relationship between age, education, knowledge, economic status, occupancy density, and clean water facilities. There is a relationship between nutritional status, DHF prevention measures, air humidity, garbage collection facilities, waste water disposal facilities with the incidence of dengue hemorrhagic fever in the Work Area of ??the Pamenang Health Centre